Pengaruh Gaya Kepemimpinan Transformasional dan Komunikasi Organisasi Terhadap Kinerja Anggota Lazismu Aceh - Afdhalul Rahman; Hasanah Hasanah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the effect of transformational leadership and organizational communication on the performance of Lazismu Aceh amil, with work motivation as an intervening variable. The study was conducted in several districts/cities in Aceh Province with active amil respondents selected through cluster sampling. The sample size was determined based on a minimum ratio of 5:1 of the number of indicators (Hair Jr. et al., 2021), so that with 27 indicators, a minimum of 135 respondents were required. Data analysis used Partial Least Square (PLS)-based Structural Equation Modeling (SEM). The results showed that transformational leadership and organizational communication had a positive and significant effect on the performance of amil, both directly and through work motivation. Work motivation was also found to have a significant positive effect on performance and acted as a mediator that strengthened the relationship between leadership, communication, and performance.These findings emphasize the importance of inspirational leadership, effective internal communication, and intrinsic motivation in enhancing the productivity and effectiveness of amil work in nonprofit organizations. The implication is that strategically strengthening leadership and communication aspects can be a key factor in optimizing the performance of Lazismu members in the zakat management environment.